La contingencia intelectual y gastronómica según Alberto Pedro Torriente: Manteca y otras necesidades alimenticias en la Cuba de los noventa - Tomé, Patricia (Latin American Theatre Review, 2016)
This article examines how Manteca by Alberto Pedro Torriente —considered the most popular and polemic Cuban dramatist of his time— conveys the idea that during Cuba’s “Special Period” literary workmanship was homologous to culinary struggles, in part due to the artistic, social, and economic circumstances of the period. The passivity set on stage by the protagonists —three middle-aged siblings forced to coexist with a pig inside a deteriorated apartment— is echoed by the shortages in foodstuffs, electricity, and gas on the island. In the midst of a forced fast, the youngest brother attempts to create an alternative self through literary writing, thus laying the foundation of an alternative reality where he can satisfy his starvation. The author argues that such artistic creations, as seen on stage, simulate a theatrical, culinary künstlerroman, wherein personal distress and famine are merged with stagnant creativity during a time of social apathy and perpetual subsistence.